Heat treatment effect in preparation of YBCO system - Ling, Jeffrey Chia Siong (2004)
The purpose for doing this project is to determine the effect of heat treatment to the superconductor on critical temperature. Three samples of YBa2Cu3O7 powder is annealed under the heat treatment of 900°C, 1000°C and 1200°C. The pellets are then tested for critical temperature, Tc by using four-point-probe machine when the temperature is increased. The mobility of the carriers depends upon temperature, crystal defect density, and all impurities present. Comparison among the Tc graphs and data are collected and drawn by with Microsoft Excel. From the results, sample which is annealed under the temperature of 900°C achieved the highest Tc which is 90K. Besides testing for Tc, the samples was also scanned with X-ray diffraction (XRD) to determine their crystal structures through lattice a, b, and c. The results showed that 900°C and 1000°C annealed samples are orthorhombic structure which stands in 3.82A, 3.80A, 11.87A and 3.85A, 3.88A, 11 .82A respectively. As a conclusion, different temperatures of the heat treatment will strongly affect its crystal structures from orthorhombic to tetragonal and critical temperature value.